2013
DOI: 10.1111/pme.12283
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Limb Pain: A Systematic Neuroanatomical-Based Review of Pharmacologic Treatment

Abstract: Currently, the best evidence (level 2) exists for the use of IV ketamine and IV morphine for the short-term perioperative treatment of PLP and PO morphine for an intermediate to long-term treatment effect (8 weeks to 1 year). Level 2 evidence is mixed for the efficacy of perioperative epidural anesthesia with morphine and bupivacaine for short to long-term pain relief (perioperatively up to 1 year) as well as for the use of gabapentin for pain relief of intermediate duration (6 weeks).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 158 publications
0
64
1
5
Order By: Relevance
“…As Jess’s exercise levels and food intake maintained her in a good body condition and she had regular health checks, she would have experienced the pleasures of being physically fit and healthy, operating without difficulty within the agility constraints imposed by her amputation [71] and exposed to minimal risk of obesity-induced arthritis in her intact hind leg in later life [72]. She exhibited no extra attention to her amputated limb, so she was not likely to have experienced pain or other unpleasant sensations in the stump or a phantom limb, common in a high proportion of human amputees [73]. The salient affective health outcomes were therefore graded “A/++”, no compromise with mid-level enhancement (Table 2; [1,18]).…”
Section: Welfare Impacts Of a Traumatic Injury In A Farm Dogmentioning
confidence: 99%
“…As Jess’s exercise levels and food intake maintained her in a good body condition and she had regular health checks, she would have experienced the pleasures of being physically fit and healthy, operating without difficulty within the agility constraints imposed by her amputation [71] and exposed to minimal risk of obesity-induced arthritis in her intact hind leg in later life [72]. She exhibited no extra attention to her amputated limb, so she was not likely to have experienced pain or other unpleasant sensations in the stump or a phantom limb, common in a high proportion of human amputees [73]. The salient affective health outcomes were therefore graded “A/++”, no compromise with mid-level enhancement (Table 2; [1,18]).…”
Section: Welfare Impacts Of a Traumatic Injury In A Farm Dogmentioning
confidence: 99%
“…B. auf die Reduktion der Erregbarkeit der läsionierten peripheren Neuronen (etwa durch Gabapentin, Carbamazepin oder durch trizyklische Antidepressiva bei Dauerschmerzen) oder die Reduktion sympathischer Aktivierung ab. Eine hohe Evidenz existiert auch für die Therapie mit Opioiden [1,26]. Die Therapie erfolgt mit retardierten Opioiden strikt nach Zeitschema.…”
Section: » Ein Großteil Derunclassified
“…Die besten Ergebnisse erbringen bislang Morphin und Ketamin i.v. mit kurzfristigem Erfolg (Evidenzniveau 2) und Medikation mit Opioiden per os für mittel-bis län-gerfristige Effekte (8 Wochen bis 1 Jahr; [1,26].…”
Section: » Ein Großteil Derunclassified
“…While it is the most common therapeutic approach, pharmaceutical treatment of PLP is supported mainly by circumstantial reports and studies have not demonstrated efficacy placebo-controlled, randomized studies 13,14. A promising alternative for unilateral amputees is mirror therapy, which allows patients to “see” their phantom limb as a reflection of the intact limb.…”
Section: Introductionmentioning
confidence: 99%